The Microbiome of Leonardo da Vinci’s Drawings: A Bio-Archive of Their History - Piñar, Guadalupe; Sclocchi, Maria Carla; Pinzari, Flavia; Colaizzi, Piero; Graf, Alexandra; Sebastiani, Maria Letizia; Sterflinger, Katja (Frontiers in Microbiology, 2020)
Seven emblematic Leonardo da Vinci’s drawings were investigated through third generation sequencing technology (Nanopore). In addition, SEM analyses were carried out to acquire photographic documentation and to infer the nature of the micro-objects removed from the surface of the drawings. The Nanopore generated microbiomes that can be used as a “bio-archive” of the drawings, offering a kind of fingerprint for current and future biological comparisons. This information might help to create a biological catalogue of the drawings (cataloging), a microbiome-fingerprint for each single analyzed drawing, as a reference dataset for future studies (monitoring) and last but not least a bio-archive of the history of each single object (added value). Results showed a relatively high contamination with human DNA and a surprising dominance of bacteria over fungi. However, it was possible to identify typical bacteria of the human microbiome, which are mere contaminants introduced by handling of the drawings as well as other microorganisms that seem to have been introduced through vectors, such as insects and their droppings, visible through the SEM analyses. All drawings showed very specific bio-archives, but a core microbiome of bacteria and fungi that are repeatedly found in this type of material as true degraders were identified, such as members of the phyla Proteobacteria, Actinobacteria and Firmicutes among bacteria, and fungi belonging to the classes Sordariomycetes and Eurotiomycetes. In addition, some similarities were observed that could be influenced by their geographical location (Rome or Turin), indicating the influence of this factor and denoting the importance of environmental and storage conditions on the specific microbiomes.